The Model of Akhlakul Karimah Development Implemented by Islamic Education Teachers at MAS Al-Wardah - Maghfuroh, Fazratun (Yayasan Rahmat Islamiyah, 2026)
This study aims to analyze the model of akhlakul karimah development implemented by Islamic Education (PAI) teachers at MAS Al-Wardah. Moral development is a fundamental aspect of Islamic education that emphasizes not only the transfer of knowledge but also character formation aligned with Islamic moral values. Employing a qualitative case study approach, the research utilizes observations, interviews, and documentation. The results reveal that PAI teachers implement several development models, including exemplary behavior (uswah hasanah), habituation, advising (mau’izhah), disciplinary reinforcement, and emotional approaches. The exemplary model is the most dominant, as students tend to imitate the daily behavior of their teachers. Moreover, the integration of religious activities such as dhuha prayers, Qur’an recitation, and daily short sermons contributes significantly to shaping students' character. The study concludes that the success of akhlakul karimah development largely depends on teachers’ consistency in providing positive examples as well as the support of a conducive school environment.